Laparoscopic Transperitoneal Approach for Vesicovaginal Repair : The First Experience in Hasan Sadikin Hospital - Jumadi Santoso; Sawkar Vijay Pramod (Ikatan Ahli Bedah Indonesia, 2014)
Background. Obstetric fistula is a severe and debilitating condition occurring throughout the developing world. Although there are no accurate data on the incidence and prevalence of the condition, the majority of vesicovaginal fistulas develop after obstetric procedure, with delayed labour accounting for 90% of cases. Several techniques are available for repairing the fistulas. Transperitoneal approaches give good results even for difficult posterior located fistulas, but are associated with increased morbidity compared with the transvaginal approach. We performed a laparoscopic repair and omentum interposition. The objective of this article is to report our first experience in transperitoneal laparoscopic repair of vesicovaginal fistula in Hasan Sadikin Hospital. Method. A 31–year–old female presented with vesicovaginal fistula after sectio caersaeran because of de- layed labour. After a failed trial of conservative treatment with catheter drainage, a transperitoneal laparoscopic repair was performed. Cystoscopy was performed initially to confirm the fistula location and for bilat- eral ureteric catheterization. A 4–port technique was performed with the patient in the position with her legs in lithotomy position. Without opening the bladder, the fistula tract was excised with separation of the bladder from the anterior vagina wall. Both the bladder and vagina walls were then closed separately using intracorporeal suturing with an interpositional omentum. Results. Total operative time was 270 min. Normal diet was resumed on day 1, drain was removed on post operative day 1 and patient was discharged on the second day with an indwelling catheter. Food cosmetic result on wound operation and no leakage under cystogram after 2 weeks. The catheter was removed after 2 weeks. Conclusion. Laparoscopic transperitoneal repair of vesicovaginal fistula with omentum inteposition is feasible in Hasan Sadikin Hospital with good outcomes, short hospital days, and good cosmetics result. Still need more same cases before a final conclusion